2022
DOI: 10.1038/s41586-022-05222-x
|View full text |Cite|
|
Sign up to set email alerts
|

Quantifying hierarchy and dynamics in US faculty hiring and retention

Abstract: Faculty hiring and retention determine the composition of the US academic workforce and directly shape educational outcomes1, careers2, the development and spread of ideas3 and research priorities4,5. However, hiring and retention are dynamic, reflecting societal and academic priorities, generational turnover and efforts to diversify the professoriate along gender6–8, racial9 and socioeconomic10 lines. A comprehensive study of the structure and dynamics of the US professoriate would elucidate the effects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
132
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(140 citation statements)
references
References 50 publications
8
132
0
Order By: Relevance
“…This result remains relatively constant between 1950 and 2019. The hierarchical structure of faculty hiring networks, that has been found in studies of other academic disciplines (Clauset et al, 2015) and of mathematics using a different data set (Wapman et al, 2022), is also observed in our analysis.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This result remains relatively constant between 1950 and 2019. The hierarchical structure of faculty hiring networks, that has been found in studies of other academic disciplines (Clauset et al, 2015) and of mathematics using a different data set (Wapman et al, 2022), is also observed in our analysis.…”
Section: Discussionsupporting
confidence: 80%
“…The result of a search is publicly known eventually, but the list of applicants and the selection criteria used are not revealed. Success in acquiring a faculty position may not only depend on an individual scholar's research productivity and academic credentials (Fernandes et al, 2020), but also on demographic factors such as race, gender, and childhood socioeconomic status (Clauset et al, 2015;Wapman et al, 2022;Morgan et al, 2022;White-Lewis, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This naturally leads to fewer self-citations for women, and it may reflect that women are less extensively included in co-authorship networks than men 27,28 . These self-citation and authorship discrepancies could contribute to the "leaky pipeline" of women in STEM 29 , which contributes to disparities in academic faculty positions [30][31][32] , editorial boards 33 , and awards 34 . Nevertheless, future work is needed to determine if and how lower self-citation rates contribute to these outcomes.…”
Section: Gender Disparities In Self-citation Ratesmentioning
confidence: 99%